2016
DOI: 10.3390/atmos7080100
|View full text |Cite
|
Sign up to set email alerts
|

Potential Sources and Formations of the PM2.5 Pollution in Urban Hangzhou

Abstract: Continuous measurements of meteorological parameters, gaseous pollutants, particulate matters, and the major chemical species in PM 2.5 were conducted in urban Hangzhou from 1 September to 30 November 2013 to study the potential sources and formations of PM 2.5 pollution. The average PM 2.5 concentration was 69 µg¨m´3,~97% higher than the annual concentration limit in the national ambient air quality standards (NAAQS) of China. Relative humidity (RH) and wind speed (WS) were two important factors responsible f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“…The major PM sources have changed from coal burning to a mixture of construction sites, coal burning, vehicle exhaust, and secondary particles. Iron/steel manufacturing, secondary aerosols, and local vehicle emissions are suggested as the main sources of PM 2.5 in Hangzhou City [29,32], with secondary inorganic aerosols playing an important role in haze formation [45]. particles.…”
Section: Temporal Distribution Of Air Pollutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The major PM sources have changed from coal burning to a mixture of construction sites, coal burning, vehicle exhaust, and secondary particles. Iron/steel manufacturing, secondary aerosols, and local vehicle emissions are suggested as the main sources of PM 2.5 in Hangzhou City [29,32], with secondary inorganic aerosols playing an important role in haze formation [45]. particles.…”
Section: Temporal Distribution Of Air Pollutantsmentioning
confidence: 99%
“…episodes [32]. Eliminating substandard vehicles, upgrading vehicle standards, supplying low-sulfur oil, and introducing alternative fuel vehicles could simultaneously reduce the four key pollutants (CO, volatile organic compounds, nitrogen oxides, and particulate matter) [28].…”
Section: Introductionmentioning
confidence: 99%
“…This is likely because that high temperature in a year could help to accelerate the photochemical reaction between precursors, further influencing the formation of particles [41]. Therefore, the effects of temperature on particle concentrations are complex [8,9]. For instance, in summer, high temperature promotes the formation of particulate sulfate, but dissociates parts of particulate nitrate [48][49][50], hence, it was hard to present the definite relationships between temperature and PM 10 and PM 2.5 concentrations.…”
Section: Effect Of Meteorological Factors On Pm 10 and Pm 25 Concentmentioning
confidence: 99%
“…Removing mass particles from the atmosphere links to many complicated physical processes, such as deposition, interception, impaction, and resuspension, and they are all related to meteorological conditions [2], including air temperature, relative humidity, and wind conditions [6,7]. Generally, temperature has an effect on atmospheric relative humidity and air turbulence [8][9][10] and increasing temperature will be followed by decreasing humidity and increasing turbulence, which as a consequence decreases PM concentration and increases resuspension at the same time [8]. The low temperature and high relative humidity have a negative relationship with particle concentrations [11], while the physical mechanism still remains blurred.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we are focusing on Hangzhou City, which is one of the central cities of the Yangtze River Delta Urban Agglomeration; we explored its atmospheric environment ( Figure 1a) and found that, as a tourist city, Hangzhou City's air quality condition was not in sufficient shape [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. Liu et al [27] analyzed the atmospheric PM 2.5 mass concentration variation characteristics in Hangzhou from 2011 to 2014 and concluded that the peak appeared in 2013 (52.2 µg/m 3 ) and is closely related to the motor vehicle emissions and changes in meteorological conditions.…”
Section: Sdrp Journal Of Earth Sciences and Environmental Studies (Issnmentioning
confidence: 99%